2014
DOI: 10.1038/tp.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

Healthy individuals treated with clomipramine: an fMRI study of brain activity during autobiographical recall of emotions

Abstract: Various functional magnetic resonance imaging studies addressed the effects of antidepressant drugs on brain functioning in healthy subjects; however, none specifically investigated positive mood changes to antidepressant drug. Sixteen subjects with no personal or family history of psychiatric disorders were selected from an ongoing 4-week open trial of small doses of clomipramine. Follow-up interviews documented clear positive treatment effects in six subjects, with reduced irritability and tension in social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In line with this, the FPS has been found to be involved in functions related to cognitive control (Laird et al, 2011). Indeed, two studies that induced irritability by recalling autobiographical experiences found increased prefrontal activation during irritability scripts compared with neutral scripts in HCs (Cerqueira et al, 2010(Cerqueira et al, , 2014. These findings suggest that our result of higher local efficiency in the FPS may act as a compensatory mechanism to control cognitively (fluctuating) feelings of irritation and frustration.…”
Section: Affective Instability and Connectomicsmentioning
confidence: 59%
“…In line with this, the FPS has been found to be involved in functions related to cognitive control (Laird et al, 2011). Indeed, two studies that induced irritability by recalling autobiographical experiences found increased prefrontal activation during irritability scripts compared with neutral scripts in HCs (Cerqueira et al, 2010(Cerqueira et al, , 2014. These findings suggest that our result of higher local efficiency in the FPS may act as a compensatory mechanism to control cognitively (fluctuating) feelings of irritation and frustration.…”
Section: Affective Instability and Connectomicsmentioning
confidence: 59%
“…Previous studies of healthy individuals who were given controlled doses of citalopram, fluvoxamine, as well as other psychotropic medications, showed drug-related variations in neural activation during a variety of fMRI tasks, suggesting that these medication may affect global network function. Additionally, there is evidence that psychotropic medications specifically affect neural recruitment during emotional processing and induce positive mood responses and affect recall of negative emotions ( Cerqueira et al, 2014 ). Therefore, while developmental alterations in the self-referential processing network from adolescence into adulthood is likely, medication effects should also not be ignored when interpreting these differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, its anticholinergic effects require further investigations, especially in the context of SARS-CoV-2 infection. Clomipramine has already been assessed in healthy volunteers (without psychiatric pathology), and was well tolerated without mood changes (e.g., mania) at the doses used for patients with mood disorders ( Cardoso de Almeida et al, 2010 ; Cerqueira et al, 2014 ).…”
Section: Summary and Perspectivesmentioning
confidence: 99%